Sensory reanimation of the hand by transfer of the superficial branch of the radial nerve to the median and ulnar nerve. Issue 12 (9th October 2016) - Schenck, Thilo L.; Lin, Shenyu; Stewart, Jessica K.; Koban, Konstantin C.; Aichler, Michaela; Rezaeian, Farid; Giunta, Riccardo E.
Abstract: Background: It remains a surgical challenge to treat high‐grade nerve injuries of the upper extremity. Extra‐anatomic reconstructions through the transfer of peripheral nerves have gained clinical importance over the past decades. This contribution outlines the anatomic and histomorphometric basis for the transfer of the superficial branch of the radial nerve (SBRN) to the median nerve (MN) and the superficial branch of the ulnar nerve (SBUN). Methods: The SBRN, MN, and SBUN were identified in 15 specimens and the nerve transfer performed. A favorable site for coaptation was chosen and its location described using relevant anatomical landmarks. Histomorphometric characteristics of donor and target were compared to evaluate the chances of a clinical success. Results: A suitable location for dissecting the SBRN was identified prior to its first bifurcation. Coaptations were possible near the pronator quadratus muscle, approximately 22 cm distal to the lateral epicondyle of the humerus. The MN and SBUN had to be dissected interfasciculary over 82 ± 5.7 mm and 49 ± 5.5 mm, respectively. Histomorphometric analysis revealed sufficient donor‐to‐recipient axon ratios for both transfers and identified the SBRN as a suitable donor with high axon density. Conclusion: Our anatomic and histomorphometric results indicate that the SBRN is a suitable donor for the MN and SBUN at wrist level. The measurements show feasibility of this procedure and shall help in planning this sensory nerve transfer. High axon density in the SBRN identifies it or its branches an ideal candidate for sensory reanimation of fingers and thumbs. Abstract : Our anatomic and histomorphometric results indicate that the SBRN is a suitable donor for the MN and SBUN. The measurements show feasibility of this procedure and shall help in planning this sensory nerve transfer. Identification of high axon density in the SBRN identifies it or its branches as an optimal candidate for sensory reanimation of the fingers and the thumb.